Movement Disorder - Intan Sahara Zein; Phonna Maghfirah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Movement disorders are neurological conditions that affect the speed, fluency, and ease of movement. Movement disorder is a neurological disease with various etiologies. There are quite a lot of clinical diseases of movement disorders in the field of neurology. Chorea is an involuntary movement that is uncontrolled and not purposeful Chorea is classified according to etiology as primary and secondary chorea. Primary chorea is idiopathic/genetic, while secondary chorea is associated with infections, metabolic and endocrine disorders, immunology, and drugs. Infectious causes such as encephalitis can have clinical manifestations in the form of chorea as a movement disorder.